IMPLEMENTASI MODEL TEAMS GAMES TOURNAMENT DALAM MENINGKATKAN KEAKTIFAN BELAJAR MURID PADA PEMBELAJARAN IPS DI SMP NEGERI 13 MALANG - Niken Dia Agustin; Djoko Soelistijo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Implementing educational reforms that allow for the freedom to design learning activities is a key focus of education in Indonesia. However, a complex issue within the Indonesian educational landscape is the low level of student engagement during the learning process. Teachers often retain full control over instruction, thereby limiting students' ability to construct knowledge independently; consequently, students may be physically present but remain socially, emotionally, and intellectually disengaged. One solution to enhance student engagement is the implementation of cooperative learning models. This study aims to measure the impact of the Teams Games-Tournament (TGT) learning model, supported by the use of Uno Stacko, on student engagement. A quantitative approach utilizing a One-Group Pretest Posttest experimental design was employed. The study sample consisted of 32 students from class 8A at SMP Negeri 13 Malang. The results indicate that the TGT learning model successfully fosters active learning. These findings demonstrate that the TGT model, supplemented by Uno Stacko, offers a potential solution to the problem of low student engagement in Social Studies (IPS) lessons.